High Carbohydrate Diet Increased Glucose Transporter Protein Levels in Jejunum but Did Not Lead to Enhanced Post-Exercise Skeletal Muscle Glycogen Recovery - Takahashi, Yumiko (Nutrients, 2021)
We examined the effect of dietary carbohydrate intake on post-exercise glycogen recovery. Male Institute of Cancer Research (ICR) mice were fed moderate-carbohydrate chow (MCHO, 50%cal from carbohydrate) or high-carbohydrate chow (HCHO, 70%cal from carbohydrate) for 10 days. They then ran on a treadmill at 25 m/min for 60 min and administered an oral glucose solution (1.5 mg/g body weight). Compared to the MCHO group, the HCHO group showed significantly higher sodium-D-glucose co-transporter 1 protein levels in the brush border membrane fraction (p = 0.003) and the glucose transporter 2 level in the mucosa of jejunum (p = 0.004). At 30 min after the post-exercise glucose administration, the skeletal muscle and liver glycogen levels were not significantly different between the two diet groups. The blood glucose concentration from the portal vein (which is the entry site of nutrients from the gastrointestinal tract) was not significantly different between the groups at 15 min after the post-exercise glucose administration. There was no difference in the total or phosphorylated states of proteins related to glucose uptake and glycogen synthesis in skeletal muscle. Although the high-carbohydrate diet significantly increased glucose transporters in the jejunum, this adaptation stimulated neither glycogen recovery nor glucose absorption after the ingestion of post-exercise glucose.